2006
DOI: 10.2320/matertrans.47.2533
|View full text |Cite
|
Sign up to set email alerts
|

Surface Free Energy of Alloy Nitride Coatings Deposited Using Closed Field Unbalanced Magnetron Sputter Ion Plating

Abstract: The sticking of product material to injection molding tools is a serious problem, which reduces productivity and reliability. Depositing alloy nitride coatings (TiN, ZrN, CrN, and TiAlCrN) using closed field unbalanced magnetron sputter ion plating and electrodeposition of chromium, and characterizing their surface free energies in the temperature range 20-120 C have led to the development of a non-sticking (with a low surface free energy) coating system for semiconductor IC packaging molding dies. The contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Table 3. Surface free energy of the surfaces at 293K [62,66]. In the case of ZrN, despite of its low polar component, the high total energy value leads to a lower contact angle than expected.…”
Section: Contact Anglementioning
confidence: 90%
“…Table 3. Surface free energy of the surfaces at 293K [62,66]. In the case of ZrN, despite of its low polar component, the high total energy value leads to a lower contact angle than expected.…”
Section: Contact Anglementioning
confidence: 90%
“…In addition, it has been reported that N 2 plasma treatment causes Ti-N bonding, resulting in the formation of a hydrophilic TiN layer at or near the surface. 19,25 Furthermore, as shown in other sources, 19 we determined that our N 2 -APP system roughened the CP-cpTi surfaces at the 10 nm level. These results indicated that the combination of chemical and topographical modifications is potentially sufficient to increase surface wettability and protein adsorption.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 This hydrophilic layer formation could also contribute to the increased surface wettability, along with the reduced relative content of carbon. In this study, we used an EDS to analyze the elemental compositions of the CP-cpTi surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…MgO is less than 1%, the interface is coherent and lattice planes are matched resulting in a small 18 (~63 mJ/m 2 ) compared to most elemental metals, (Al,Sc)N is likely to have even lower surface energy and sharper cusps in the Wulff plot, as it is a semiconductor with saturated bonds and high ionicity. Under these conditions, the free (Al,Sc)N surface would be expected to be faceted to a greater degree than the free TiN surface.…”
Section: X-ray Reflectivitymentioning
confidence: 99%